2021
DOI: 10.3390/ma14133644
|View full text |Cite
|
Sign up to set email alerts
|

Laser Powder Bed Fusion of Chromium Bronze Using Recycled Powder

Abstract: Laser powder bed fusion (LPBF) of Cu-0.5Cr was carried out using recycled powder taken out from the LPBF machine after previous printing. Various volumetric defects characterized the powder wherein particle size distribution was the same as virgin powder. Using recycled powder resulted in extra spherical pore formation after the LPBF process. Despite that, a relative density of 99.2% was achieved by LPBF parameters optimization. Solidified microstructure with a small volume of defects consisted of an oversatur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 37 publications
(51 reference statements)
0
3
0
Order By: Relevance
“…In various works devoted to LPBF technology, it has been shown that the well-chosen initial powder material is the basis for the successful consolidation with minimum defects [ 31 , 32 , 33 , 34 , 35 ]. The most important properties of the powder are particle morphology, chemical composition, and microstructure [ 31 ].…”
Section: Resultsmentioning
confidence: 99%
“…In various works devoted to LPBF technology, it has been shown that the well-chosen initial powder material is the basis for the successful consolidation with minimum defects [ 31 , 32 , 33 , 34 , 35 ]. The most important properties of the powder are particle morphology, chemical composition, and microstructure [ 31 ].…”
Section: Resultsmentioning
confidence: 99%
“…Apart from the several common alloys mentioned above, several studies on powder reusability of other alloy systems, including Co-Cr-based alloys [200,260,261], Cu alloys [262], and high entropy alloys [263], have also been conducted, which are described in turn in the following.…”
Section: Powder Reusability Of Other Alloy Systemsmentioning
confidence: 99%
“…Though several studies have been conducted for L-PBF Cu alloy [162], there is limited research on powder reusability of Cu alloy powders. To the best of our knowledge, only one study [262] focuses on the reusability of chromium bronze. It was found that the chromium bronze printed with reused powders exhibited a YS of (136.8 ± 8.7) MPa, a UTS of (187.4 ± 10.1) MPa, and an elongation of (15.5 ± 2.3)%.…”
Section: Powder Reusability Of Other Alloy Systemsmentioning
confidence: 99%